The Effect of Irregular Stimulation on the Development of Reflective Thinking among Art Education Students (Journal of the College of Basic Education, 2026)
Irregular Stimulation and Its Effect on the Development of Reflective Thinking among Art Education Students.The researcher found that the problem of the research lies in the necessity of studying irregular stimulation because of its importance and influence on all educational phenomena in any educational situation, and its relationship with other variables, including reflective thinking. Therefore, the research problem was framed by the following question: What is irregular stimulation and its effect on the development of reflective thinking among art education students?The aim of the research was to identify irregular stimulation and its effect on the development of reflective thinking among art education students. The limits of the research were as follows: the spatial limit was the Department of Art Education, College of Fine Arts, University of Baghdad; the temporal limit was the first semester of the academic year (2024–2025); the human limit was second-year students of the Department of Art Education; and the subject limit was irregular stimulation and the development of reflective thinking.To achieve the objective of the research, the researcher adopted the experimental design with partial control for two groups, one experimental and the other control. The research sample was selected randomly and consisted of (47) male and female students distributed into two groups. The experimental group was represented by Section (B) with (21) students after excluding one female student due to failure because of absence, while the control group was represented by Section (D) with (22) students after excluding three male students who failed due to absence. Thus, the final sample size became (43) students.The researcher prepared a measurement tool represented by a reflective thinking test. The research procedures continued for a period of (10) weeks, starting from Thursday, 2024/10/17, until Thursday, 2024/12/19. After using the t-test (T-test), the researcher reached the most important results, which indicated the significant role of irregular stimulation in developing reflective thinking, as it makes students the main محور of the educational situation and develops their skills in perceiving relationships, in addition to increasing their ability to analyze and compare concepts and multiple relationships through reflecting on the educational situation of the lesson.Based on the results of the research, the researcher reached several conclusions, including that irregular stimulation contributes to consolidating information in students’ minds and developing their reflective thinking for a longer period compared with the traditional method. Moreover, the use of irregular stimulation in teaching the subject of aesthetic education adds an element of motivation and concentration in linking ideas, concepts, and artistic terminology.